Funkcje kształtowania kompetencji medialnych uczniów w procesie edukacyjnym współczesnej szkoły - Романюк, Світлана; Василик, Марина (Studia Gdańskie. Wizje i rzeczywistość., 2023)
The article, based on the analysis of normative sources, educational, methodological and scientific literature, substantiates the peculiarities of forming media literacy of schoolchildren of general secondary education, identifies the principles and reveals the tasks of media education in the context of today's challenges, and clarifies the possibilities of school subjects in forming the mass media literacy of a growing personality. The study found that the basic goals of media education in the formation of media literacy of schoolchildren are: development of students' communication skills; formation of critical thinking; learning information perception, recoding of a visual image into a verbal sign system; assessing the quality of information, developing the ability to choose when "consuming" information from the media; raising the general cultural level of the individual. It has been proven that media literacy plays an important role in the formation of a personality, because without it, effective learning and development, the ability to navigate the excessive flow of information, the ability to analyze and critically comprehend the information and media texts received are impossible. Since the foundation of many processes is laid at school age, it is very important to help schoolchildren acquire theoretical knowledge and practical skills in the field of media literacy. In this context, an important role belongs to the teacher, who must know and understand what media, media literacy, fakes, etc. are and use them in their daily activities, form the opinion and worldview of students, teach them to navigate the global media space. It has been determined that the educational process can be carried out through electronic resources and the possibilities of their integration into educational activities can be considered in order to involve schoolchildren in the creation of various types of media content during reflection. It is proved that the leading role in this process belongs to school subjects in Ukrainian/native language, reading, computer science, “Civic education”, etc. The author emphasizes the use of tasks/exercises in the language and literary field of education that develop skills in working with educational information and promote a critical attitude towards it.
Keywords: media literacy, media education, media space, infomedia literacy, mass media, manipulation, media texts, school subjects.